2018
DOI: 10.1080/15384101.2018.1560203
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Downregulation of NEAT1 reverses the radioactive iodine resistance of papillary thyroid carcinoma cell via miR-101-3p/FN1/PI3K-AKT signaling pathway

Abstract: Considering the resistance of papillary thyroid cancer (PTC) 131 I therapy, this study was designed to find a solution at molecular respect. By probing into lncRNA-NEAT1/miR-101-3p/FN1 axis and PI3K/AKT signaling pathway, this study provided a potential target for PTC therapy. 131 I-resistant cell lines were established by continuous treatment with median-lethal 131 I. Bioinformatic analysis was applied to filtrate possible lncRNA/miRNA/mRNA and related signaling pathway. Luciferase reporter assay was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…However, NEAT1 was also reported to interact with many other miRNAs. For example, NEAT1 was reported to sponge miR-101 in non-small cell lung cancer [34], papillary thyroid carcinoma [35], hepatocellular carcinoma [36] and breast cancer [11]. Besides, NEAT1 sponged miR-124 in neuroblastoma [37], retinoblastoma [38], Alzheimer's disease [38] and nasopharyngeal carcinoma [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, NEAT1 was also reported to interact with many other miRNAs. For example, NEAT1 was reported to sponge miR-101 in non-small cell lung cancer [34], papillary thyroid carcinoma [35], hepatocellular carcinoma [36] and breast cancer [11]. Besides, NEAT1 sponged miR-124 in neuroblastoma [37], retinoblastoma [38], Alzheimer's disease [38] and nasopharyngeal carcinoma [39].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are small noncoding RNAs which could negatively regulate the expression of the target genes by directly binding their 3′-UTRs [24]. It has been found that the deregulation of miRNA expression is a common feature of many types of human cancers, including thyroid cancer [25,26]. Accumulated evidence has demonstrated that the aberrant expression of miRNAs plays crucial roles in cancer initiation and progression [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of NEAT1 lowers the radioactive iodine resistance of the cells by targeting miR-101-3p to regulate FN1 in papillary thyroid carcinoma through the alteration of PI3K-AKT signaling. 27 Therefore, we suggested that NEAT1 could modulate cell behavior by interacting with a specic target gene in CC. vitro and in vivo by targeting DAB2IP in esophageal squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%